Politik Santun Kaum Santri (Pendidikan Politik Bagi Pemilih Pemula Kalangan Santri) - Nashiruddin, Ahmad (Abdimas Indonesian Journal, 2025)
The purpose of this service is to provide polite political education to students related to the current political year situation. This is considered important because political literacy that is still low will make them feel full of guidance. In the end, many of them just participate in politics without paying attention to the good or bad. The service method used in this community service is ABCD (Asset Based Community Development) with the main asset being the students of the Majlis Ta'lim Al-hikmah Islamic Boarding School (PERMATA) who are potential novice voters. The practice of service starts from observation, FGD, socialization, mentoring, and evaluation. The results of the service concluded that one way to provide an understanding of polite politics to students in Pati Regency is to provide education related to what polite politics is, its practices, and how to apply it. This method can also provide understanding to students regarding what can and cannot be done to implement political actions in a polite manner. That polite politics is higher than just practical politics that is dirty and legalizes all means.